Faraid Literacy Education: Understanding the System of Inheritance Distribution Based on Islamic Law for Family Welfare - Taryanto; Muhammad Ridwan; Sulistri; Halimatussadiah; Gusti Randy Pratama; Abdul Rohman; Hariyanti; Min Sahril (Pascasarjana Universitas Mataram, 2025)
The division of inheritance in Islam, known as faraid, has detailed legal rules and aims to maintain justice and harmony in the family. However, the low public literacy of this system often causes conflicts and inequality in the distribution of inheritance. This research aims to improve public understanding of faraid law through a systematic educational approach. The method used is qualitative descriptive with a field study approach based on extension activities. The results showed that the public's understanding of the concept of faraid increased significantly after educational interventions, which was characterized by increased awareness of inheritance rights and reduced potential for family conflicts. These findings indicate that good faraid literacy not only strengthens the equitable application of Islamic law, but also contributes to the long-term well-being and harmony of the family. Education on faraid law systematically and based on counseling has proven to be effective in increasing public understanding, reducing potential inheritance conflicts, and strengthening the application of justice values in Islamic law. Therefore, faraidh literacy needs to be integrated into religious and social programs to support family harmony and welfare.